The concordance of directly and indirectly measured built environment attributes and physical activity adoption - O'Connor Daniel P; Medina Ashley; Mama Scherezade K; McAlexander Kristen M; Lee Rebecca E (BMC, 2011)
Background Physical activity (PA) adoption is essential for obesity prevention and control, yet ethnic minority women report lower levels of PA and are at higher risk for obesity and its comorbidities compared to Caucasians. Epidemiological studies and ecologic models of health behavior suggest that built environmental factors are associated with health behaviors like PA, but few studies have examined the association between built environment attribute concordance and PA, and no known studies have examined attribute concordance and PA adoption. Purpose The purpose of this study was to associate the degree of concordance between directly and indirectly measured built environment attributes with changes in PA over time among African American and Hispanic Latina women participating in a PA intervention. Method Women (N = 410) completed measures of PA at Time 1 (T1) and Time 2 (T2); environmental data collected at T1 were used to compute concordance between directly and indirectly measured built environment attributes. The association between changes in PA and the degree of concordance between each directly and indirectly measured environmental attribute was assessed using repeated measures analyses. Results There were no significant associations between built environment attribute concordance values and change in self-reported or objectively measured PA. Self-reported PA significantly increased over time (F(1,184) = 7.82, p = .006), but this increase did not vary by ethnicity or any built environment attribute concordance variable. Conclusions Built environment attribute concordance may not be associated with PA changes over time among minority women. In an effort to promote PA, investigators should clarify specific built environment attributes that are important for PA adoption and whether accurate perceptions of these attributes are necessary, particularly among the vulnerable population of minority women.